Retinal ganglion cells death in glaucoma – mechanism and potential treatment. Part I. - Rokicki, Wojciech; Dorecka, Mariola; Romaniuk, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Glaucoma is a kind of optic neuropathy where selective retinal ganglion cell loss is the major hallmark. Frequently glaucoma is associated with elevated intraocular pressure, but this condition is neither necessary nor sufficient for onset and progression of the disease. The exact mechanism of ganglion cell death in glaucoma and fully effective treatment of glaucomatous neuropathy still remain unknown. This article is a review of the recent researches relevant to IOP independent risk factors, mechanisms of RGC death and modern potential therapeutic strategies in glaucoma. Part one includes review of blood flow changes, neurotrophic factors deprivation and apoptotic dysregulation findings in glaucoma